Implikasi Yuridis Pemberlakuan Wacana Earth to Earth Transportation oleh SpaceX - Loijens, Tasya Ester (CV Rewang Rencang, 2020)
The rapid development of technology allows humans to utilize natural resources that were previously difficult to reach even as resources contained in space. With these advances, the law also contributes through international law governing aspects related to the use of space often known as the Five United Nations Treaties on Outer Space. In 2017, the CEO of SpaceX (an American private aerospace company), Elon Musk, announced plans to use transportation previously used to move objects from Planet Earth to Space, rockets, to be used as public transportation used as a means of mobilization from one place to another on Planet Earth. This is interesting because the concept of using Space after planet Earth's air surface thus giving rise to new contemplation related to licensing and aspects of its legality. In this paper, the author intends to examine from the perspective of international law with international arrangements relating to the laws of air and space.